Analisis Penggunaan Sistem Accurate dalam Pencatatan Transaksi Kas pada PT XYZ - Rozak, Mochamad Akbar; Sulistyowati, Erna (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This research aims to analyze the implementation of the Accurate accounting system in the cash transaction recording process at PT XYZ, a cement distributor company focused in eastern Indonesia, particularly in East Nusa Tenggara. Along with business growth, the company transitioned from manual recording using Microsoft Excel to a computerized system to enhance efficiency and accuracy. This study employs a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The analysis focuses on comparing processes before and after the use of Accurate, its contribution to efficiency, and the challenges faced during implementation. The research results show that the Accurate system significantly improves efficiency by automating journal processes, minimizing human error, and presenting financial data in real-time and structured formats. However, challenges related to discipline in timely transaction input were found, causing discrepancies between system balances and bank statements. The solution to these challenges is to improve the finance team's discipline in performing daily data input.